Pengembangan Media Pembelajaran Teka-Teki Silang “Keberagaman Kebudayaan Indonesia” Muatan Pelajaran IPS bagi Peserta Didik Kelas IV Sekolah Dasar - Vera Yuli Erviana (UM Purwokerto Press, 2022)
This research is motivated by the limited use of learning media that has not been varied, only using textbooks as teaching materials and posters of cultural map images. This study aims to determine the steps of media development and to determine the quality of product development in the form of a crossword puzzle learning media book